Naturalized Epistemology and the Law of Evidence: Methodological Reflections - Michael S. Pardo (Quaestio Facti)
This paper discusses Ronald Allen’s article, Naturalized Epistemology and the Law of Evidence Revisited, and reflects on how epistemology can contribute to our understanding of the evidentiary proof process. I first situate Allen’s critique of recent philosophical scholarship, distinguishing between general theoretical accounts of proof (including the theory that Allen and I have defended), on one hand, and the applications of specific epistemological concepts or issues to law, on the other. I then present a methodological picture that diverges in some respects from the one that emerges from Allen’s critique. In discussing this alternative methodological picture, I explain how epistemology can contribute to legal evidence and proof while avoiding the problems that Allen identifies.